Role of oral health during COVID-19 - Mani, Koushiki; Karini, Johnny (International Journal of Research in Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) caused by novel coronavirus severe acute respiratory syndrome coronavirus 2 [SARS-Cov-2] has challenged the health care system worldwide. Currently, more than 43 million people are affected by this disease worldwide.1 The risk factors known to develop complications of COVID-19 are age along with comorbidities like diabetes, hypertension, obesity, cardiovascular diseases, COPD, CKD etc. This same population is also at risk for developing oral diseases. Other known risk factors for oral diseases are smoking, alcohol consumption. Preliminary reports suggest that there may be a connection between SARS-CoV-2 infections and the microbial load in the oral cavity.2 Yoon et al reported that SARS-CoV-2 viral load was consistently high in the saliva in the early stages of COVID-19.3 Few studies report that oral hygiene interventions in patients with pneumonia have drastically improved clinical outcome.4,5 Researchers also reported that improved oral care significantly reduces the incidence of ventilator-associated pneumonia in patients in an intensive care unit.6 Thus oral health is extremely important in the current pandemic of COVID-19.